КӨРКЕМ ӘДЕБИЯТ ТИЛИ ҲӘМ ОНДАҒЫ КӨРКЕМ СҮЎРЕТЛЕЎ УСЫЛЛАРЫНЫҢ ҚОЛЛАНЫЛЫЎЫ - Балтабаева, Д.Б. (FAN va JAMIYAT, 2025)
The article is devoted to describing the features of literary language, which is one of the areas of modern linguistics. The study analyzes the use of artistic techniques in the novels of English and Karakalpak writers. Based on the four main sections of linguopoetics are identified the individual stylistic features of each author.